Village stratification for policy analysis: Multiple development domains in the Ethiopian highlands - Kruseman, Gideon K.; Pender, J.L.; Tesfay, G.; Gebremedhin, Berhanu (International Food Policy Research Institute, 2002)
This paper presents a method for stratifying villages into Development domains using multivariate analysis of a broad community-based survey. The results from the analysis are used to draw conclusions in terms of policy implications. Topics of discussion include Development domains and policy implications. The paper ends with comment by Samuel Benin.